The spectrum of gastrointestinal ischemia: 2010 - Brandt, Lawrence J. (Henry Stewart Talks, 2011)
Ischemic disease of the gastrointestinal tract manifests a spectrum of injury that includes ischemic colitis, acute mesenteric ischemia, focal segmental ischemia and intestinal angina, each with its own presentations, management strategies, and outcomes, This lecture will review fundamental s of each of the types of ischemic damage to the gastrointestinal tract
Archived at 2022/02/27